Nigeria - Niven, Sir Rex. (London : Ernest Benn Limited, 1967)
The book is an attempt to describe the complicated country of Nigeria in as many aspects as possible
Includes bibliographical references and index.
ijb 18/01/2019
Loans
Keywords: British Colony; History; Nigeria